The Effect of Chronic and Inhospital Exposure to Renin-Angiotensin System Inhibitors on the Outcome and Inflammatory State of Coronavirus Disease 2019 Adult Inpatients - Gaspar, Pedro (Int J Hypertens, 2021)
BACKGROUND: Controversies exist about the effect of renin-angiotensin system inhibitors (RASi) on coronavirus disease 2019 (COVID-19) outcome. The inhospital use of RASi and its effect on inflammatory sate are still poorly studied during the COVID-19 pandemic. OBJECTIVES: We aimed to compare the impact of previous and inhospital RASi exposure on the outcome and inflammatory response of COVID-19 patients. METHODS: Single-centre, ambispective analysis of hospitalized adult COVID-19 patients at Hospital de Santa Maria, Lisbon, between March and August 2020 was performed. We excluded asymptomatic patients and those admitted due to another disease. The primary outcome was inhospital all-cause mortality. Illness severity was assessed based on the development of acute respiratory distress syndrome/acute lung injury (ARDS/ALI), intensive care unit (ICU) admission, and need for invasive mechanical ventilation (IMV). We used C-reactive protein (CRP), ferritin, and interleukin 6 (IL-6) as surrogate markers of the inflammatory response. RESULTS: From a total of 432 patients, 279 were selected, among whom 133 (47.7%) were receiving a RASi. Chronic treatment with RASi was not associated with the risk of death (OR 1.24, 95% CI 0.66–2.31, p=0.500), ARDS/ALI development (OR 1.12, 95% CI 0.67–1.86, p=0.676), ICU admission (OR 1.11, 95% CI 0.67–1.84, p = 0.686), and IMV need (OR 1.03, 95% CI 0.58–1.84, p=0.917) in a univariable and multivariable analysis. Inhospital RASi withdrawing was associated with the risk of death (OR 4.38, 95% CI 1.11–17.21, p=0.035) and ARDS/ALI development (OR 4.33, 95% CI 1.49–12.6, p=0.007), the latter remaining significant after adjustment. Previous exposure to RASi was associated with lower CRP levels at admission (p=0.018). IL-6 levels were significantly higher in those patients whose RASi were stopped (p=0.024). CONCLUSION: Previous and inhospital exposure to RASi was not associated with mortality nor severity of COVID-19. This study supports current guidance on RASi management during the COVID-19 pandemic.